Gendered Violence at International Festivals 2020
DOI: 10.4324/9780429344893-7
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualising safety and crime at UK music festivals

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Drawing on data from a larger study exploring the extent, nature, scope, and responses to sexual violence at UK music festivals (Bows et al, 2020(Bows et al, , 2022, this article focuses on qualitative interviews undertaken with 13 victim-survivors of unwanted sexual attention at festivals. As this part of the study focused on subjective, situated experiences of sexual violence, an inductive, qualitative approach was adopted.…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Drawing on data from a larger study exploring the extent, nature, scope, and responses to sexual violence at UK music festivals (Bows et al, 2020(Bows et al, , 2022, this article focuses on qualitative interviews undertaken with 13 victim-survivors of unwanted sexual attention at festivals. As this part of the study focused on subjective, situated experiences of sexual violence, an inductive, qualitative approach was adopted.…”
Section: The Studymentioning
confidence: 99%
“…While the survey findings and media reports give some indication of the extent of sexual harassment and assault at festivals, there are major gaps in knowledge about the prevalence, nature, experiences, and responses to sexual violence. This article presents data from the first UK study to explore women's experiences of sexual violence at UK music festivals, contributing to the small but growing body of literature in this area (Aborisade, 2021;Baillie et al, 2021;Bows et al, 2020Bows et al, , 2022Fileborn et al, 2020) and to the broader literature on gendered experiences of leisure spaces (Aitchison, 1999;Green & Singleton, 2006;Gunby et al, 2020;Hill et al, 2020;Stevenson, 2017).…”
mentioning
confidence: 99%
“…They found that drug and alcohol consumption and overcrowding were the factors participants most associated with feeling unsafe at a festival, and such experiences profoundly affect women's ability to fully participate in music festivals. A study by Durham Law School found that more women than men are concerned about sexual harassment and safety at festivals (Marsh, 2018; Bows et al , 2020). Some festivals have responded to the pervasiveness of sexual harassment and assault (and ensuing negative media coverage) by having women-only areas and other segregationist strategies (Beaumont-Thomas, 2017).…”
Section: Events As Gendered Spaces and Practicesmentioning
confidence: 99%